2010
DOI: 10.1111/j.1399-3038.2009.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbon metabolite levels and pediatric allergy and asthma in an inner-city cohort

Abstract: Exposure to polycyclic aromatic hydrocarbons (PAH) has been associated with allergic sensitization and asthma. We hypothesized that increased urinary PAH metabolites are associated with allergy or asthma among children age 5 yrs in an inner-city birth cohort. As part of an ongoing prospective birth cohort under the auspices of the Columbia Center for Children's Environmental Health (CCCEH), urine was collected from 5-yr-old children (n = 222) of Dominican American and African American mothers in Northern Manha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 39 publications
3
56
2
1
Order By: Relevance
“…However tobacco smoke is comprised of thousands of constituents including polycyclic aromatic hydrocarbons (PAH). PAH exposures have been shown to cause immunological changes,13 and have been associated with wheeze and changes in IQ14 as well as allergic sensitisation 15. The PAH concentrations measured in our study are to our knowledge the first to be reported inside a vehicle with an active cigarette smoker.…”
Section: Introductionmentioning
confidence: 56%
“…However tobacco smoke is comprised of thousands of constituents including polycyclic aromatic hydrocarbons (PAH). PAH exposures have been shown to cause immunological changes,13 and have been associated with wheeze and changes in IQ14 as well as allergic sensitisation 15. The PAH concentrations measured in our study are to our knowledge the first to be reported inside a vehicle with an active cigarette smoker.…”
Section: Introductionmentioning
confidence: 56%
“…TRAP contains nontailpipe emissions from brakes and tires, and tailpipe emissions in the ultrafine particulate range (<100 nm in aerodiameter). These include trace metals and a high fraction of black and organic carbons, which have been associated with significant adverse health effects (28,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…36 CCCEH also showed that the presence of elevated levels of the urinary PAH metabolites 3-hydroxyfluorene, 3-hydroxyphenanthrene, 2-hydroxynaphthalene, 2-hydroxyflourene and 1-hydroxyphenanthrene concentrations, were associated with elevated cat-IgE levels at age 5 years in multivariate analyses. 37 In additional work utilizing annual spatial data on the proximity and density of roadways and built environment that were collected for a 250 m buffer around a child’s home, associations between geographic information systems (GIS) indicators (eg concurrent proximity to highway) and total IgE levels were found. Positive associations also were observed between percent commercial building area and asthma, wheeze, and IgE.…”
Section: Update On Pollutant Effects On Immune Mechanismsmentioning
confidence: 99%